Phytochemical Screening, GCMS Analysis and Antibacterial Activity of Moringa oleifera Ethanolic and aqueous Leaf Extracts against Some Clinical Isolates - Umaru Abdulmalik; Zuwaira Halliru; Anas Umar; Mujahid Musa; Abubakar Adam Sunusi (UMYU Journal of Microbiology Research)
In response to the escalating concerns surrounding antibiotic resistance and associated side effects, interest in plant extracts and bioactive compounds derived from medicinal herbs has been resurgent. This study investigates the Phytochemical Screening, Gas Chromatography-Mass Spectrometry (GCMS) Analysis, and Antibacterial Activity of Moringa oleifera Leaf Extracts against clinical isolates. Utilizing aqueous and ethanolic extractions, the study determined the yield percentages as 16.25% and 7.14%, respectively. Phytochemical analysis revealed the presence of alkaloids, tannins, flavonoids, glycosides, steroids, terpenoids, and saponins in both extracts, with the absence of phenol. The antibacterial activity was assessed using the agar well diffusion method, showing inhibitory effects against the tested isolates. The ethanolic extract exhibited superior antibacterial activity, with a maximum zone of inhibition (17mm) against Pseudomonas aeruginosa at 800mg/ml. The aqueous extract demonstrated a maximum zone of inhibition (12mm) against the same bacterium at the same concentration. Comparative analysis with standard antibiotics revealed competitive inhibitory effects, especially against Staphylococcus aureus and Pseudomonas aeruginosa. Furthermore, GCMS analysis identified sixteen phytochemical compounds in the ethanolic extract and eleven in the aqueous extract. The findings underscore the significant antibacterial potential of Moringa oleifera extracts, particularly against Staphylococcus aureus and Pseudomonas aeruginosa. The GC-MS results provide crucial insights into the bioactive chemical profile, supporting the potential therapeutic applications of Moringa oleifera in combating various infections. This study contributes valuable knowledge to exploring alternative treatments amid growing antibiotic resistance concerns.